Advances in business and management forecasting. Vol. 14 - Lawrence, Kenneth D.; Klimberg, Ronald K. (Advances in business and management forecasting., 2021)
Volume 14, Advances in Business and Management Forecasting is a blind refereed serial publication. It presents state-of-the-art studies in the application of forecasting methodologies in such areas as financial forecasting, market demand analysis, executive compensation forecasting, data analysis, forecasting improvement with interpolation and cluster analysis. This is a key text for academics and researchers of financial forecasting, market demand forecasting and executive compensation forecasting.